The polyhydroxyalkanoate genes of a stress resistant Antarctic Pseudomonas are situated within a genomic island - Ayub, Nicolás Daniel; Pettinari, María Julia; Mendez, Beatriz Silvia; López, Nancy Irene (Plasmid)
Pseudomonas sp. 14-3 is an Antarctic bacterium that shows high stress resistance in association with high polyhydroxybutyrate (PHB) production. In this paper genes involved in PHB biosynthesis (phaRBAC) were found within a genomic island named pha-GI. Numerous mobile elements or proteins associated with them, such as an integrase, insertion sequences, a bacterial group II intron, a complete Type I protein secretion system and IncP plasmid-related proteins were detected among the 28 ORFs identified in this large genetic element (32.3 kb). The G + C distribution was not homogeneous, likely reflecting a mosaic structure that contains regions from diverse origins. pha-GI has strong similarities with genomic islands found in diverse Proteobacteria, including Burkholderiales species and Azotobacter vinelandii. The G + C content, phylogeny inference and codon usage analysis showed that the phaBAC cluster itself has a complex mosaic structure and indicated that the phaB and phaC genes were acquired by horizontal transfer, probably derived from Burkholderiales. These results describe for the first time a pha cluster located within a genomic island, and suggest that horizontal transfer of pha genes is a mechanism of adaptability to stress conditions such as those found in the extreme Antarctic environment. Fil: Ayub, Nicolás Daniel. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Química Biológica de la Facultad de Ciencias Exactas y Naturales. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Química Biológica de la Facultad de Ciencias Exactas y Naturales; Argentina Fil: Pettinari, María Julia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Química Biológica de la Facultad de Ciencias Exactas y Naturales. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Química Biológica de la ...